2018
DOI: 10.1002/ijc.31233
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fecal immunochemical tests for colorectal cancer screening

Abstract: Fecal immunochemical tests (FITs) for hemoglobin (Hb) are increasingly used for colorectal cancer (CRC) screening. We aimed to review, summarize and compare reported diagnostic performance of various FITs. PubMed and Web of Science were searched from inception to July 24, 2017. Data on diagnostic performance of quantitative FITs, conducted in colonoscopy-controlled average-risk screening populations, were extracted. Summary receiver operating characteristic (ROC) curves were plotted and correlations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 49 publications
7
38
0
Order By: Relevance
“…The other systematic review quantified performance characteristics for both CRC and advanced adenoma, but only included studies of high-risk persons (18). In addition, our searches identified a recent systematic review by Gies and colleagues that assessed seven FIT brands across 22 studies (60). Although less comprehensive than ours and despite inclusion of at least one study that contained persons with previous neoplasia (61), Gies and colleagues found areas under receiver operating characteristics curves similar to our findings, and determined that the large degree of heterogeneity reflected variations in test thresholds (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other systematic review quantified performance characteristics for both CRC and advanced adenoma, but only included studies of high-risk persons (18). In addition, our searches identified a recent systematic review by Gies and colleagues that assessed seven FIT brands across 22 studies (60). Although less comprehensive than ours and despite inclusion of at least one study that contained persons with previous neoplasia (61), Gies and colleagues found areas under receiver operating characteristics curves similar to our findings, and determined that the large degree of heterogeneity reflected variations in test thresholds (60).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our searches identified a recent systematic review by Gies and colleagues that assessed seven FIT brands across 22 studies (60). Although less comprehensive than ours and despite inclusion of at least one study that contained persons with previous neoplasia (61), Gies and colleagues found areas under receiver operating characteristics curves similar to our findings, and determined that the large degree of heterogeneity reflected variations in test thresholds (60). Our findings are also consistent with a recent analysis by Selby and colleagues that considered repeated (i.e., programmatic) testing with FIT, quantifying CRC detection at various test thresholds (62).…”
Section: Discussionmentioning
confidence: 99%
“…Participants received trial medication (allocated in a blinded manner for both physicians and participants according to randomization list), questionnaire, and patient diary. In addition, participants received 4 stool collection kits for each of 2 FITs: FOB Gold Tube Screen (Sentinel Diagnostics), a widely used quantitative FIT, 8,15,16 and the FD Hb/Hp Complex quick (Frost Diagnostika), a qualitative chromatographic FIT, 17 referred to as quantitative and qualitative FIT hereafter. At the time this trial was planned, both quantitative and qualitative FITs were widely used in Germany.…”
Section: Trial Design and Trial Populationmentioning
confidence: 99%
“…[9][10][11] FITs detect the majority (70%-80%) of CRCs at high (>90%) specificity but only a minority of advanced adenomas, the precursors of most CRCs. 8,10 Detecting advanced adenomas in addition to CRCs could make a major contribution to effectiveness of FIT-based CRC screening. 12 Improved sensitivity without simultaneously decreasing specificity could improve the performance of FIT for colorectal cancer screening.…”
mentioning
confidence: 99%
“…Low-literacy instruction is thus an effective and necessary first step toward ensuring proper FIT completion and, ultimately, successful CRC screening. Although FIT performance characteristics are an important consideration and may differ across brands depending on positivity threshold and immunoassay technique, 16,17 FIT manufacturers also should see the value of seeking competitive differentiation through pictorial, patient-friendly instructions. To carry forward the momentum from the 80% by 2018 initiative into the next decade, physicians and health care stakeholders should hold FIT manufacturers accountable for both the accessibility and performance of their tests.…”
mentioning
confidence: 99%